Internal defect detection using laser-generated longitudinal waves in ablation regime - Choi, Sungho; Jhang, Kyung-Young (Journal of mechanical science and technology, 2018)
Laser ultrasonics could be an attractive solution for the nondestructive testing of structures in harsh environments. Longitudinal waves generated in the ablation regime are especially well suited to internal defect detection because they provide a higher signal-to-noise ratio in comparison to ultrasonic waves generated under a thermo-elastic regime, while their propagation direction normal to the surface enables the simplified interpretation processing of received signals when the defect echoes are analyzed. The internal defect detection using laser-generated longitudinal waves in the ablation regime was investigated numerically and experimentally, and a numerical model to simulate the generation and propagation of ultrasonic waves in the ablation regime was developed. This model was based on the simulation of ultrasonic generation and propagation caused by the net reaction force that was directly converted from the laser intensity absorbed onto the surface. This model was also extended as a model for internal defect detection. A steel specimen containing artificial internal defects was fabricated and inspected by using the through-transmission (T-scan) and pulse-echo (B-scan) modes. Clear amplitude reduction was observed in the transmitted waves at the defect positions in T-scan images, while B-scan images clearly showed the defect echoes arriving at different times depending on the depth location of internal defects. These results demonstrate that longitudinal waves excited in the ablation regime can be effectively used for internal defect detection.